2020
DOI: 10.21164/pomjlifesci.722
|View full text |Cite
|
Sign up to set email alerts
|

Properties and use of rosemary (Rosmarinus officinalis L.)

Abstract: Rosemary (Rosmarinus officinalis L.) is a spice herb found in most cuisines and in many spice blends on the Polish market. It deserves special attention, not only because of its unique taste and smell, but also due to a composition that provides health benefits. Its antimicrobial activity has been proven in relation to bacteria, fungi (including yeast) and viruses. Positive effects on the metabolism of carbohydrates and lipids, and the function of the nervous system, as well as hepatoprotective properties have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Verlaging van de pH van het spijsverteringskanaal draagt bij aan verhoogde renninesecretie die stolselvorming bevordert en verbeterde verteerbaarheid bewerkstelligt (Pearlin et al, 2019). Rozemarijn (Rosmarinus officinalis) heeft krachtige antioxiderende activiteit , ontstekingsremmende eigenschappen , werkt als spijsverteringstimulant (Erdogrul, 2002), stimuleert de eetlust (Asressu et al, 2014)) en verbetert de stofwisseling (Pawlowska et al, 2020). Rode zonnehoed (Echinacea purpurea) heeft antioxiderende activiteit , werkt immunostimulerend en -modulerend (Dobrange et al, 2019), werkt ontstekingsremmend (Gu et al, 2023), antiviraal en schimmelwerend (Mir-Rashed et al, 2010).…”
Section: Onderzoekunclassified
“…Verlaging van de pH van het spijsverteringskanaal draagt bij aan verhoogde renninesecretie die stolselvorming bevordert en verbeterde verteerbaarheid bewerkstelligt (Pearlin et al, 2019). Rozemarijn (Rosmarinus officinalis) heeft krachtige antioxiderende activiteit , ontstekingsremmende eigenschappen , werkt als spijsverteringstimulant (Erdogrul, 2002), stimuleert de eetlust (Asressu et al, 2014)) en verbetert de stofwisseling (Pawlowska et al, 2020). Rode zonnehoed (Echinacea purpurea) heeft antioxiderende activiteit , werkt immunostimulerend en -modulerend (Dobrange et al, 2019), werkt ontstekingsremmend (Gu et al, 2023), antiviraal en schimmelwerend (Mir-Rashed et al, 2010).…”
Section: Onderzoekunclassified
“…The majority of studies identified linalool (20-45%) and linalyl acetate (25 to 46%) as the main components of lavender essential oil. Research concerning lavender properties mainly emphasizes their antifungal, antibacterial, and antioxidant activities [20][21][22][23][24][25][26][27]. Sarkhosh et al (2018) identified in Lavandula angustifolia L. about 19 detectable compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It was emphasized conducted study that rosemary has some beneficial effects on the nervous system works and lipid metabolism. (Pawłowska et al, 2020). There were around 150 different compounds identified in rosemary essential oil (REO).…”
Section: Introductionmentioning
confidence: 99%